Early Medieval Copper-Alloy Metalworking at Rendlesham, Suffolk, England. Issue 2 (3rd July 2022) - Blakelock, Eleanor; Martinón-Torres, Marcos; Scull, Christopher
Abstract : THE 5TH- TO 8TH-CENTURY METAL-DETECTED ASSEMBLAGE FROM RENDLESHAM includes material representing the manufacture of copper-alloy and precious metal objects in the later 6th and 7th centuries. This study of the copper alloys focuses on the evidence for manufacturing technology, sets it against the evidence for alloy compositions and metal supply from the wider assemblage, and considers the scale and organisation of production at the site. Examination by optical microscopy of key traits on metalworking waste and unfinished objects has made it possible to identify the types of mould being used and to reconstruct a sequence of manufacture for objects made at Rendlesham. Compositional analysis by XRF and SEM-EDS shows the expected range of alloys for 5th- to 8th-century England and confirms recycling as the main source of metal. Lead isotope analysis, applied here for the first time to early medieval copper alloys from England, also indicates recycling over the long term. There is no evidence for a supply of fresh metal, or for working in brass, before the 7th century. The results contribute to a wider understanding of copper-alloy metalworking practice and metal supply in early medieval England, and establish the potential of metal-detected material as evidence for the study of non-ferrous metalworking.